Probabilistic Stress Intensity Factor Prediction of Surface Crack Using Bootstrap Sampling Method - Husnain, M.N.M.; Akramin, M.R.M.; Chuan, Z.L.; Shaari, M.S.; Takahashi, Akiyuki; Akmal, M.H. (International Journal of Integrated Engineering, 2022)
Fatigue cracks commonly occur for in-service engineering structures. The main parameter for fatigue crack is the stress intensity factor (SIF). The SIF is an indicator of the fatigue crack growth and remaining life of a structure. Nonetheless, a problem was raised when determining the remaining life since the SIF could not be presented in physical phenomena. Thus, a technique is required to predict the range of SIF. Maximum and minimum bounds of SIF help estimate the range of remaining life. This paper aims to predict a structure’s safe and failure region during the fracture process based on the SIFs. The primary tool is S-version Finite Element Model (S-FEM). Yet, S-FEM unable to compute random variables in analysis. Thus, the Bootstrap is developed and embedded into S-FEM for computing random variables in the analysis. The random variables are utilised to predict a range of SIFs. The SIFs are generated based on one hundred samples. The samples are randomly generated based on the distribution of material properties. A lognormal distribution is used to generate the material properties. The sampling process is computed based on the bootstrap method. The embedded Bootstrap in S-FEM was introduced as BootsrapS-FEM. When the samples exceed the fracture toughness of 29 MPa.?m, the failure region is indicated at the angle 2?/? = 0.627 to 1 with 6% of failure samples. The safe region is observed at angle 2?/? = 0 to 0.626 with 94% of the samples. The failure region is essential in this analysis to prevent unstable crack growth.